Moving up the copper value chain in Southern Africa - Neva Makgetla; Saul Levin; Sithembiso Mtanga (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
Southern African countries-mainly Zambia and the Democratic Republic of the Congo-account for around a seventh of global production of copper. In the 2010s, they imported over a third of the associated capital goods and components from South Africa. Given this strength, some observers suggest that the South African capital goods industry could do more to support copper fabrication in the region. Theoretically, investing in production of semi-manufactures (principally wire, cable, and tubing) would promote industrialization and enhance value-add. In practice, however, unit prices have only been slightly higher for semis than for refined copper, limiting scope for fabrication-especially as local manufacturers obtain copper essentially at international prices. In any case, the South African capital goods industry is centred on mining, not metalworking machinery. It can only compete with overseas suppliers if it obtains increased financial support for exports and for research and development.
Keywords: L52; L6; L7; O14; 330; capital equipment; copper; industrialization; industrial clusters; mineral beneficiation; Southern African Development Community; value chains